Five-year mortality and readmission rates in patients with heart failure in India: Results from the Trivandrum heart failure registry. (1st March 2021) - Harikrishnan, Sivadasanpillai; Jeemon, Panniyammakal; Ganapathi, Sanjay; Agarwal, Anubha; Viswanathan, Sunitha; Sreedharan, Madhu; Vijayaraghavan, Govindan; Bahuleyan, Charantharayil G.; Biju, Ramabhadran; Nair, Tiny; Pratapkumar, N.; Krishnakumar, K.; et al.
Abstract: Introduction: Heart failure (HF) has emerged as an important and increasing disease burden in India. We present the 5-year outcomes of patients hospitalized for HF in India. Methods: The Trivandrum Heart Failure Registry (THFR) recruited consecutive patients admitted for acute HF among 16 hospitals in Trivandrum, Kerala in 2013. Guideline-directed medical therapy (GDMT) was defined as the combination of beta-blockers (BB), renin angiotensin system blockers (RAS), and mineralocorticoid receptor antagonists (MRA) in patients with HF with reduced ejection fraction (HFrEF, EF < 40%) at discharge. We used Cox proportional hazards models and Kaplan-Meier survival plots for analysis. The MAGGIC risk score variables were included as exposure variables. Results: Among 1205 patients [69% male, mean (SD) age = 61.2 (13.7) years], HFrEF constituted 62% of patients and among them, 25% received GDMT. The 5-year mortality rate was 59% ( n  = 709 deaths), and median survival was 3.1 years. Sudden cardiac death and pump failure caused 46% and 49% of the deaths, respectively. In the multivariate Cox model, components of GDMT associated with lower 5-year mortality risks were discharge prescription of BB, RAS blocker, and MRA. Older age, lower systolic blood pressure, NYHA class III or IV, and higher serum creatinine were also associated with higher 5-year mortality. Conclusions: Three out of every 5 patients had died during 5-years of follow-up with a median survival of approximately 3 years. Lack of GDMT in patients with HFrEF and frequent readmissions were associated with higher 5-year mortality. Quality improvement programmes with strategies to improve adherence to GDMT and reduction in readmissions may improve HF outcomes in this region. Highlights: The THFR is the first heart failure registry in India with 5-year follow-up and low attrition rate. Median survival time of HF patients in the Trivandrum Heart Failure Registry(THFR) is 3.1 years. In this relatively younger cohort of HF patients, 3 out of 5 patients had died at 5-years. Those who received guideline directed medical therapy at discharge from index hospitalization(25%) had better survival. Interventions aimed at increasing guideline directed medical therapy may improve HF outcomes in India.